The Characteristics of Tafsir Al-Mizan by Thabathaba'iy - Wahid, Abdul; Ibrahim, Mazlan (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Tafsir al-Mizan is known as one of the main tafsir books among the Shi'a scholars. However, the book is read and analyzed by groups other than Shi'a scholars. Sunni scholars, too, use this tafsir book to help them understand the verses of the Quran. This article will explore the factors that make al-Mizan's interpretation accepted by Sunni scholars and examine the characteristics of the book of Tafsir al-Mizan, such as the method of interpretation, the style of interpretation, and the scholars of interpretation. This study showed that the interpreter is an adherent of the Shi'a Itsna Ashariah scholars, so some of his interpretations tend toward Shi'a thought in certain matters, such as the issue of the imamate. However, in general, this interpretation is not only a reference for adherents and the Shi'a scholars but is also used as reading material by Muslims of the Sunni scholars. The specialty of the interpretation lies in the strength of the interpreter who displays it, which is primarily derived from the Qur'an itself. As a scholar with a great soul, he took many sources of interpretation from previous books of tafsir, even from scholars other than Shi'a. As for the source of the interpretation of the hadith, it comes more from the books of hadith among the Shi'a.